Immunogenicity and Safety of the Influenza A/H1N1 2009 Inactivated Split-Virus Vaccine in Young and Older Adults: MF59-Adjuvanted Vaccine versus Nonadjuvanted Vaccine - Cheong, Hee Jin (American Society for Microbiology, 2011)
Since initial reports in April 2009, the pandemic influenza A (H1N1) virus has spread globally. Influenza vaccines are the primary method for the control of influenza and its complications. We conducted a multicenter clinical trial to evaluate the immunogenicity and safety of H1N1 vaccine (Green Cross Co.) in young adults (18 to 64 years) and the elderly (≥65 years) using a two-dose regimen, with the doses administered 21 days apart. Three different regimens of hemagglutinin antigen were comparatively analyzed: 3.75 μg (MF59 adjuvanted) versus 7.5 μg (MF59 adjuvanted) versus 15 μg (nonadjuvanted) in young adults and 3.75 μg (MF59 adjuvanted) versus 7.5 μg (MF59 adjuvanted) in the elderly. In young adults, all three vaccine regimens met the European Agency for the Evaluation of Medicinal Products (EMA) criteria after the first dose. In the elderly, on day 21 after the first dose, the rates of seroprotection and seroconversion were significantly higher for the 7.5-μg dose of MF59 adjuvanted vaccine than for the 3.75-μg dose (58.0% versus 44.3% [P = 0.03] and 53.7% versus 37.2% [P < 0.01], respectively). After the second dose, the geometric mean titer (GMT) increment was blunted with a 15-μg dose of nonadjuvanted vaccine, whereas the GMT increased about 2-fold with MF59 adjuvanted vaccines. In conclusion, a single 7.5-μg dose of MF59 adjuvanted vaccine would have a practical advantage over a two-dose, 3.75-μg, MF59 adjuvanted vaccine priming schedule. Following a two-dose priming schedule, the increase in hemagglutinin inhibition titers was higher with MF59 adjuvanted vaccine than with nonadjuvanted vaccine.